2020
DOI: 10.3390/brainsci10080481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Epilepsy in Pediatric Patients with Cerebral Palsy

Abstract: Cerebral palsy (CP) is a set of etiologically diverse symptoms that change with the child’s age. It is one of the most frequent causes of motor disability in children. CP occurs at a frequency of 1.5 to 3.0 per 1000 live-born children. CP often coexists with epilepsy, which is drug-resistant in a high number of cases. The aim of the present study was to analyze the associations between preconception, prenatal, perinatal, neonatal, and infancy risk factors for epilepsy in a group of pediatric patients with CP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
5
19
2
Order By: Relevance
“…On the other hand, Baumfeld et al conducted a prospective cohort study and demonstrated that cesarean section was an independent factor affecting neurological disorders in children along with birth weight, maternal age, Apgar score, gestational age and the sex of the neonate [83]. Recent data by Sadowska et al [84] demonstrated that delivery by cesarean section increased the risk of epilepsy over two-fold (OR 2.17) in the patients with cerebral palsy. Deoni et al [111] demonstrated for the first time that caesarean section may be related with changes in brain development, at least during early infancy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Baumfeld et al conducted a prospective cohort study and demonstrated that cesarean section was an independent factor affecting neurological disorders in children along with birth weight, maternal age, Apgar score, gestational age and the sex of the neonate [83]. Recent data by Sadowska et al [84] demonstrated that delivery by cesarean section increased the risk of epilepsy over two-fold (OR 2.17) in the patients with cerebral palsy. Deoni et al [111] demonstrated for the first time that caesarean section may be related with changes in brain development, at least during early infancy.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by El-Tallawy et al [ 18 ], neonatal seizures can be a strong predictor of epilepsy in cerebral palsy. Sadowska et al [ 19 ] investigated 181 children with CP and selected 102 children affected by epilepsy (56.35%); among this group, 44 (43%) had drug-resistant epilepsy and only 15 (14.71%) were responsive to treatment. Epilepsy was more frequent in CP children with quadriplegia (75%), ataxia (83%), and mixed forms (80%) in comparison to diplegia (32%) and hemiplegia (38%).…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy was more frequent in CP children with quadriplegia (75%), ataxia (83%), and mixed forms (80%) in comparison to diplegia (32%) and hemiplegia (38%). Maternal hypertension is considered to be a relevant risk factor for epilepsy in CP children, for which Sadowska et al [ 19 ] reported in their study an odds ratio (OR) of 12.46 ( p = 0.0001), while for drug-resistant epilepsy, they reported an OR of 9.86 ( p = 0.040) [ 19 ]. Other risk factors are represented by delivery by cesarean section, for which the risk of epilepsy in CP children is double (OR = 2.17, p = 0.0129), neonatal seizures with a risk for CP epilepsy calculated as an OR of 3.04 ( p = 0.011), and drug-resistant epilepsy with an OR of 4.02 ( p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…We excluded epilepsy patients because of the documented multifold risk of unintentional injuries, including injuries causing death among persons with epilepsy in both clinic‐based and population‐based studies 12,13 . Persons with infantile cerebral palsy were excluded because of their severe motor, gait, balance, vestibular, and oculomotor function disruptions, which highly predispose them to injury in addition to high prevalence of epilepsy (>50%) that also predisposes them to injury 14,15 . In addition, we excluded patients with a diagnosis of injury within 1 year prior to the index date ( n = 63,456).…”
Section: Methodsmentioning
confidence: 99%